The Evaluation of Visual Clarity and Comfort of Light Environment in Multimedia Classroom. (29th September 2022) - Dong, Yu; Xi, Minshen; Hu, Minghua
Abstract : In order to clarify the quantitative relationship between students' visual clarity, comfort, and environmental brightness in the light environment of multimedia classrooms in colleges and universities and obtain the threshold and influence trends of brightness, visual clarity, and visual comfort in the light environment of the multimedia classroom, this paper proposes the research on the relevant influence parameters of the light environment of the multimedia classroom. Based on the analysis of the current situation of multimedia use in China, this paper proposes taking brightness as the main parameter of indoor light environment evaluation to carry out students' subjective evaluation experiments. The brightness range that can reflect the visual clarity and visual comfort of the experimenter is extracted by using multimedia combined with screen projection and HDRI technology. Finally, by analyzing the experimental data, combined with the operational definition of the psychophysical threshold, the functional relationship between visual clarity, comfort, and brightness in the light environment of a multimedia classroom is obtained through regression analysis and the threshold and extreme point data are calculated. The experimental results show that when the brightness range is 370.83 cd/m 2  ≤ X ≤ 558.47 cd/m 2, it has better visual clarity and visual comfort. When the brightness contrast is close to 10 : 1, the visual clarity is the highest; when the brightness contrast is close to 5 : 1, the visual comfort is the highest and decreases on both sides with the change in its value. Conclusion . The results of this experimental study can provide a basis for formulating and revising relevant laws and regulations in the future and provide a reference for the light environment design of multimedia classrooms in China.